Andrographis paniculata extract induced apoptosis of adenocarcinoma mammae in C3H mice - Nugrahaningsih Nugrahaningsih; Sarjadi Sarjadi; Edi Dharmana; Hartanto Wahyu Subagio (Faculty of Medicine, Universitas Trisakti, 2013)
BACKGROUNDApoptosis plays an important role in tumorigenesis. Induction of apoptosis is a strategy for developing cancer therapy. In vitro study found that andrographolide isolated from Andrographis paniculata has anticancer activity by an apoptotic mechanism in cancer cell lines. The aim of the present study was to prove theeffect of Andrographis paniculata extract administered orally on apoptosis of mammary adenocarcinoma in C3H mice.METHODSThis study was of post test randomized control group design. Twenty four C3H mice with transplanted mammary adenocarcinomas were divided into four groups. To three groups Andrographis paniculata extract was administered orally for14 days, at doses of 5, 10 and 15 mg/day, respectively, whereas to the control group no Andrographis paniculata extract was administered. On day 15 the mice were terminated. The mammary adenocarcinomas were examined by the terminal deoxynucleotide transferase dUTP nick end labeling (TUNEL) method. The values of the apoptotic index were expressed as mean±SD and analyzed using ANOVA and Pearson’s correlation test.RESULTSThe mean apoptotic index values differed significantly among the experimental groups (p=0.001). The highest value was found in the group receiving Andrographis paniculata extract 15 mg/day, while the lowest was in the control group, the values being significantly correlated (r=0.974).CONCLUSIONSOral administration of Andrographis paniculata extract induced apoptosis in C3H mice with mammary adenocarcinoma